Sirtuin-3 Protects Cochlear Hair Cells Against Noise-Induced Damage via the Superoxide Dismutase 2/Reactive Oxygen Species Signaling Pathway - Liang, Wenqi; Zhao, Chunli; Chen, Zhongrui; Yang, Zijing; Liu, Ke; Gong, Shusheng (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial oxidative stress is involved in hair cell damage caused by noise-induced hearing loss (NIHL). Sirtuin-3 (SIRT3) plays an important role in hair cell survival by regulating mitochondrial function; however, the role of SIRT3 in NIHL is unknown. In this study, we used 3-TYP to inhibit SIRT3 and found that this inhibition aggravated oxidative damage in the hair cells of mice with NIHL. Moreover, 3-TYP reduced the enzymatic activity and deacetylation levels of superoxide dismutase 2 (SOD2). Subsequently, we administered adeno-associated virus-SIRT3 to the posterior semicircular canals and found that SIRT3 overexpression significantly attenuated hair cell injury and that this protective effect of SIRT3 could be blocked by 2-methoxyestradiol, a SOD2 inhibitor. These findings suggest that insufficient SIRT3/SOD2 signaling leads to mitochondrial oxidative damage resulting in hair cell injury in NIHL. Thus, ameliorating noise-induced mitochondrial redox imbalance by intervening in the SIRT3/SOD2 signaling pathway may be a new therapeutic target for hair cell injury.